Single Diamond Scratching of Cf/SiC Composite: Force and Material Removal Mechanism Study - Zhang, Yonggang (International Journal of Mechanical and Electrical Engineering, 2025)
As one of the ceramic matrix composites (CMCs), carbon fiber-reinforced silicon carbide matrix (Cf/SiC) composites have become ideal materials for various engineering applications due to their outstanding properties. Precision surface grinding technology has been widely applied in the machining of CMC composites; however, the material removal mechanism of Cf/SiC composites remains incompletely elucidated. To reveal the material removal mechanism during the grinding of Cf/SiC composites, we designed and conducted single-abrasive scratch tests. Experimental parameters, particularly cutting speed, were aligned with actual grinding processes. Results indicate that grinding parameters—feed rate, cutting depth, and cutting direction—significantly influence grinding force and surface integrity. Impact at the tool tip and abrasive action are the primary causes of material removal. During the grinding of Cf/SiC composites, the predominant material removal mode is brittle fracture. This is because the damage behavior of Cf/SiC composites is primarily a combined manifestation of matrix cracking, fiber fracture, and fiber/matrix interface debonding. These findings are rationally explained based on the material properties and microstructural damage characteristics of the composites.